2018
DOI: 10.1111/iju.13549
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of cernitin pollen extract (Cernilton®) for 30 days might be useful to avoid unnecessary biopsy in prostate biopsy candidates: A preliminary study

Abstract: The present study is the first to show that an ideal protocol using cernitin pollen extract has the potential to avoid an unnecessary prostate biopsy procedure in patients with elevated prostate-specific antigen, possibly caused by inflammation. Additional studies with greater numbers of participants are required to confirm our findings and develop an ideal protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…The results presented in this study revealed that Cernitin® treatment was able to significantly reduce AR and PSA levels, albeit lesser than finasteride. The decrease of PSA value is also demonstrated in a recent clinical study (Togo et al, 2018). A simultaneous decrease in cell proliferation of both cell lines was found after treatment with Cernitin®.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The results presented in this study revealed that Cernitin® treatment was able to significantly reduce AR and PSA levels, albeit lesser than finasteride. The decrease of PSA value is also demonstrated in a recent clinical study (Togo et al, 2018). A simultaneous decrease in cell proliferation of both cell lines was found after treatment with Cernitin®.…”
Section: Discussionsupporting
confidence: 59%
“…Numerous clinical studies have shown that Cernitin® treatment significantly reduced prostatic volume in patients presenting with BPH (Buck, Cox, Rees, Ebeling, & John, 1990;Preuss et al, 2001). Furthermore, these clinical studies confirmed the efficacy of this drug by the relief of CP/CPPS symptoms and suppression of prostate-specific antigen (PSA) (Togo et al, 2018). In addition to clinical reports, the efficacy of Cernitin® in the inhibition of proliferation and inflammation has been validated in preclinical studies (Asakawa et al, 2001;Kamijo, Sato, & Kitamura, 2001;Talpur, Echard, Bagchi, Bagchi, & Preuss, 2003).…”
mentioning
confidence: 92%
“…In the European Association of Urology guidelines, phytotherapy, including Cernitin pollen extract (Cernilton ® ), is recommended for patients with inflammatory prostate pain syndrome, with no known reports of severe adverse events associated with its administration. If such a non-antimicrobial drug can effectively reduce serum prostate specific antigen (PSA) in prostate biopsy candidates with chronic inflammation of the prostate, an optimal method including that could be developed for avoidance of an unnecessary biopsy" [160]. Thus, to verify this possibility, Togo et al [160] administered Cernitin pollen extract tablets to prostate biopsy candidates for 30 days, before carrying out a prostate biopsy procedure.…”
Section: Chronic Prostatitismentioning
confidence: 99%
“…If such a non-antimicrobial drug can effectively reduce serum prostate specific antigen (PSA) in prostate biopsy candidates with chronic inflammation of the prostate, an optimal method including that could be developed for avoidance of an unnecessary biopsy" [160]. Thus, to verify this possibility, Togo et al [160] administered Cernitin pollen extract tablets to prostate biopsy candidates for 30 days, before carrying out a prostate biopsy procedure. Then, they evaluated the relationship between the reduction in serum PSA levels and prostate biopsy outcomes.…”
Section: Chronic Prostatitismentioning
confidence: 99%
“…22 When comparing the beneficial effects of the two drugs on prostate inflammation, cernitin might suppress inflammation more effectively in prostate tissue than tadalafil. Togo et al 23 reported that oral administration of cernitin for 30 days significantly reduced the mean serum PSA level by 0.6 ng/mL (mean reduction of 7.6%). Meanwhile, to our knowledge, there has been no report demonstrating that tadalafil reduced the serum PSA level in patients with LUTS/BPH and/or CP/CPPS.…”
Section: Discussionmentioning
confidence: 99%